From Planning to Practice: A Qualitative Inquiry into Pre-Service Teachers' Experiences - Emy Nur Rokhani; Yuyun Yulia; Lusi Nurhayati; Bunga Putri Maulia; A Nur Inayatul Aini (Pedagogy Review, 2026)
This study examines the experiences of pre-service teachers during their practicum in primary schools, especially how they designed and delivered English for Children (EFC) programs. It focuses on how they planned lessons, organized their classes, reflected on their teaching experiences, and highlighted the challenges and opportunities that arose. Twenty-two students participated, distributed among five different primary schools. The data were collected through Focus Group Discussions and analyzed using a descriptive qualitative approach. The analysis is based on the thematic analysis method of Braun and Clarke (2006). The findings show that many pre-service teachers lack self-confidence, struggle in dealing with young learners, and have problems with effective communication. However, these challenges also offered growth opportunities. Over the course of the practicum, they gradually acquired 21st-century skills such as collaboration, creativity, adaptability, and effective communication. The experience deepened their understanding of teaching English to children and made them realize the importance of reflecting on what they learned in class. In short, although the teaching practice can be challenging, this study shows that it is an important opportunity for future teachers to improve their skills, become flexible, and develop into reflective educators.Keywords: 21st century skills, descriptive qualitative study, English for children, pre-service teachers, thematic analysis